The Human Intestinal IgA Response; Burning Questions - Spencer, Jo; Fraser, Louise D. (Frontiers in Immunology, 2012)
Understanding the cellular and molecular mechanisms that generate the human intestinal IgA response is fundamentally important if effective mucosal vaccination is to be successful and broadly applied. There have been several major advances in this field recently that have allowed us to feel optimistic that this will be achieved. However, there are still many unanswered questions. These questions have been used as a scaffold for this review that considers findings at the current leading edge alongside the many uncertainties in this field.